2019
DOI: 10.1186/s12968-019-0542-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of caffeine on myocardial perfusion reserve assessed by semiquantitative adenosine stress perfusion cardiovascular magnetic resonance

Abstract: Background: Adenosine is used in stress perfusion cardiac imaging to reveal myocardial ischemia by its vasodilator effects. Caffeine is a competitive antagonist of adenosine. However, previous studies reported inconsistent results about the influence of caffeine on adenosine's vasodilator effect. This study assessed the impact of caffeine on the myocardial perfusion reserve index (MPRI) using adenosine stress cardiovascular magnetic resonance imaging (CMR). Moreover, we sought to evaluate if the splenic switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(67 reference statements)
0
6
0
1
Order By: Relevance
“…Several other studies reported on the effects of coffee intake on cardiac MRI measures yet with the focus on perfusion measurements on stress cardiac MRI [ 69 , 70 , 71 ]. Interestingly, Greulich et al showed that two cups of coffee one hour before the examination caused a significant decrease in the ischemic stress, compared to caffeine-naïve adenosine stress cardiac MRI, probably due to coronary hyperemia [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies reported on the effects of coffee intake on cardiac MRI measures yet with the focus on perfusion measurements on stress cardiac MRI [ 69 , 70 , 71 ]. Interestingly, Greulich et al showed that two cups of coffee one hour before the examination caused a significant decrease in the ischemic stress, compared to caffeine-naïve adenosine stress cardiac MRI, probably due to coronary hyperemia [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seitz et al [165] in their study showed that caffeine reduced the myocardial perfusion reserve index (MPRI). The authors examined 25 patients (84% male, median age 69 years) with substantial myocardial ischemia and coffee addiction (3-4 cups per day), who underwent repeat adenosine stress perfusion imaging by cardiovascular magnetic resonance after a prior intake of two cups of coffee (about 200 mg of caffeine) 1 h before examination, which confirmed the need for abstinence from caffeine [165].…”
Section: Caffeine and Arrhythmiamentioning
confidence: 98%
“…As a nonselective competitive inhibitor of A 2A Rs, caffeine might attenuate the vasodilator effect of adenosine, and increase sympathetic activity, yielding to capillary de-recruitment and leading to decreased myocardial perfusion reserve [47,164]. Seitz et al [165] in their study showed that caffeine reduced the myocardial perfusion reserve index (MPRI). The authors examined 25 patients (84% male, median age 69 years) with substantial myocardial ischemia and coffee addiction (3-4 cups per day), who underwent repeat adenosine stress perfusion imaging by cardiovascular magnetic resonance after a prior intake of two cups of coffee (about 200 mg of caffeine) 1 h before examination, which confirmed the need for abstinence from caffeine [165].…”
Section: Caffeine and Arrhythmiamentioning
confidence: 99%
“…J Cardiovasc Magn Reson. 2019 Jun 24;21(1):33 [ 17 ] Shusterman et al High-energy external defibrillation and transcutaneous pacing during MRI: feasibility and safety [ 18 ] Thompson et al . * Quantification of lung water in heart failure using cardiovascular magnetic resonance imaging [ 10 ] Walheim et al Multipoint 5D flow cardiovascular magnetic resonance—accelerated cardiac- and respiratory-motion resolved mapping of mean and turbulent velocities [ 19 ] * 2020 Pohost Award Winner ** 2020 Pohost Award Runner-up …”
Section: Pohost and Pennell Awardsmentioning
confidence: 99%